2017
DOI: 10.1038/srep46276
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Polycomb Group Protein Pcgf1 Severely Compromises Proper Differentiation of Embryonic Stem Cells

Abstract: The Polycomb repressive complex 1 (PRC1) is essential for fate decisions of embryonic stem (ES) cells. Emerging evidence suggests that six major variants of PRC1 complex, defined by the mutually exclusive presence of Pcgf subunit, regulate distinct biological processes, yet very little is known about the mechanism by which each version of PRC1 instructs and maintains cell fate. Here, we disrupted the Pcgf1, also known as Nspc1 and one of six Pcgf paralogs, in mouse ES cells by the CRISPR/Cas9 technology. We sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 49 publications
4
27
0
3
Order By: Relevance
“…AP staining of mESC colonies was done following the manufacturer's instructions (Yeasen). Cell cycle analysis has been described previously (46). Propidium iodide (PI) staining of mESCs was performed according to the manufacturer's instructions (Vazyme).…”
Section: Colony Formation Ap Staining and Flow Cytometrymentioning
confidence: 99%
“…AP staining of mESC colonies was done following the manufacturer's instructions (Yeasen). Cell cycle analysis has been described previously (46). Propidium iodide (PI) staining of mESCs was performed according to the manufacturer's instructions (Vazyme).…”
Section: Colony Formation Ap Staining and Flow Cytometrymentioning
confidence: 99%
“…Murine ESC-derived neural progenitor not known [281] RING1B Human melanoma lines UTX, p300 recruitment [280] Mouse spermatogonia, in vivo Interaction activator (SALL4) [257] RING1A, RING1B Mouse epithelial cells in vivo not known [250,282] PCGF5 Murine ESC-derived neural progenitor not known [283] Reporter constructs, established cell lines p300 recruitment (AUTS2) [32] PCGF1 Murine ESCs not known [284] PCGF2/MEL18 Murine ESC-derived cardiac-mesoderm precursors not known [33] EZH1 Murine myoblast line RNApolII elongation [56]…”
Section: Cbx8mentioning
confidence: 99%
“…Additionally, NSPc1 serves an important role in stemness maintenance of octamer (oct)-sex determining region of the Y chromosome-box 2 (Sox2)-homeobox protein nanog axis by directly activating the promoter of Oct4 in P19 embryonic carcinoma stem cells (14) and overexpression of Nspc1 induces ESC to self-renew independent of leukemia inhibitory factor in the culture media in vitro (15). Furthermore, Yan et al (16) recently demonstrated that although the Nspc1 mutant cells were viable and retained normal self-renewal capabilities, they presented with severe defects in differentiation. Additionally, NSPc1 regulates retinoic acid response element to downregulate p21Waf1/COP1 interacting protin-1, which is associated with the differentiation and metastasis of tumor cells (17).…”
Section: Introductionmentioning
confidence: 99%